2014
DOI: 10.3390/rs6021137
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and Modelling Spatial Variation in Soil Salinity in the Al Hassa Oasis Based on Remote Sensing Indicators and Regression Techniques

Abstract: Soil salinity is one of the most damaging environmental problems worldwide, especially in arid and semi-arid regions. An integrated approach using remote sensing in addition to various statistical methods has shown success for developing soil salinity prediction models. The aim of this study was to develop statistical regression models based on remotely sensed indicators to predict and map spatial variation in soil salinity in the Al Hassa oasis. Different spectral indices were calculated from original bands o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
49
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(58 citation statements)
references
References 68 publications
8
49
1
Order By: Relevance
“…The SI was utilized in this study because: (1) the identification of the spectral response model of saline soils is effective in the separation of saline soil types [7]; and (2) the red waveband (620~680 nm) of ETM+ image is sensitive to soil salinity [9]. Studies [7,40] found that the blue and red wavebands of Landsat data performed high spectral reflectance for salt-affected soils at low moisture content.…”
Section: Spectral Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The SI was utilized in this study because: (1) the identification of the spectral response model of saline soils is effective in the separation of saline soil types [7]; and (2) the red waveband (620~680 nm) of ETM+ image is sensitive to soil salinity [9]. Studies [7,40] found that the blue and red wavebands of Landsat data performed high spectral reflectance for salt-affected soils at low moisture content.…”
Section: Spectral Indicesmentioning
confidence: 99%
“…Salt-affected soils can be discriminated using the visible and infrared portions of remote sensing spectra [2,[6][7][8][9]. A growing body of studies, aided by statistical analyses of field spectroscopy data and satellite remote sensing observations demonstrates that both multispectral [10][11][12][13][14][15] and hyperspectral passive reflectance data can be used to map soil salinization at landscape scales [16].…”
Section: Introductionmentioning
confidence: 99%
“…Dry areas are naturally prone to soil salinization due to a lower rate of rainfall and high evaporation which limits the leaching of salts, and this effect is expected to be magnified when it is combined with humans' negative intrusion like the over-fertilization of farmland (Metternicht and Zinck, 2009). Allbed et al (2014) found that the Salinity Index (SI) and red band (band 3) have significant correlation with electrical conductivity (EC). Though much research has been carried out in the field of soil salinity identification so far, through various models like SI, Normalized Differential Salinity Index (NDSI) etc., an extraction of soil salinity still needs more accuracy because of the confusion created from the same spectral signature values of settlement roofs and saline-affected zones in the study region.…”
Section: Extraction Of Saline-affected Soilmentioning
confidence: 99%
“…The satellite images were processed with specific mathematical algorithms in all remotesensing techniques with the goal of the generation of useful information. The information mentioned can be integrated with other information and layers for the evaluation and interpretation of exploratory results (Li et al, 2015, Abedi et al, 2012Bonham-Carter and Agterberg, 1990;Carranza, 2009;Carranza and Sadeghi, 2010;Ford and Blenkinsop, 2008;Lindsay et al, 2014;Lisitsin et al, 2013;Pan and Harris, 2000;Porwal et al, 2010;Feizi and Mansouri, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous work such as Allbed et al (2014), modelling and mapping of mineral potentials based on satellite image data and processing it based on remote-sensing and regression analysis is a promising approach as it facilitates timely detection with a low-cost procedure and allows decision makers to decide what necessary action should be taken as the first step in the mineral prospectivity mapping (MPM) field.…”
Section: Introductionmentioning
confidence: 99%